CULVERT DESIGN ANALYSIS USING HY-8 SOFTWARE TO DRAIN SURFACE RUNOFF DISCHARGE AT CV GUNUNG BATUJAJAR, WEST BANDUNG REGENCY, WEST JAVA, INDONESIA - Andrew Christian; Heri Prasetya (Syarif Hidayatullah State Islamic University, 2022)
CV Gunung Batujajar is a company engaged in the mining of industrial minerals in the form of andesite that applies an open-pit mining system (surface mining). Regarding the mining drainage system that is applied, there are still obstacles in dealing with drainage problems. The flow of rainwater in CV Gunung Batujajar generally flows in two places, to the large opening pit in the south with a percentage of 70% water flow and to the north by 30%. After further review, 30% of the water flow turned out to be flowing towards residents' housing and causing the water to overflow until it was flooded, thus disrupting the productivity of the population. Therefore, the authors conducted research related to the analysis of the drainage system using a culvert. In conducting the research, the authors took several types of data such as rainfall data for 10 years, field data on road geometry conditions, etc. With a planned rainfall value of 157.06 mm/day and a planned rainfall intensity of 54.45 mm/hour obtained the design runoff discharge is 0.35 m3/s. For the culvert design at the first outlet, a trapezoidal shape design is used with a base length of 0.225 m and a height of 0.2 m. As for the design at the second outlet, it is in the form of a trapezoid with a base length of 1.2 m and a height of 1.3 m. The second outlet is concluded to be more technically secure.